2020
DOI: 10.3390/jcm9030802
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of Tumor Suppressor Mutations in Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia is mainly characterized by a complex and dynamic genomic instability. Next-generation sequencing has significantly improved the ability of diagnostic research to molecularly characterize and stratify patients. This detailed outcome allowed the discovery of new therapeutic targets and predictive biomarkers, which led to develop novel compounds (e.g., IDH 1 and 2 inhibitors), nowadays commonly used for the treatment of adult relapsed or refractory AML. In this review we summarize the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 182 publications
(227 reference statements)
0
27
1
Order By: Relevance
“…The Wilms’ tumor 1 ( WT1 ) gene, whose protein product acts as a transcription factor, regulating cell development and survival and whose quantitative assessment is a useful tool to measure disease burden in AML [ 14 , 27 , 28 ], was overexpressed in either the peripheral blood or bone marrow in 17 of 19 (89.5%) evaluable BCL-2 − AML patients and in 57 of 60 (95.0%) evaluable BCL-2 + AML patients. In line with the lower bone marrow blast percentage, the WT1 transcript burden in the bone marrow was significantly lower in the BCL-2 − AML subgroup (47,910 ± 24,410 copies/µg) as compared with the BCL-2 + subgroup (148,900 ± 23,700 copies/µg; p = 0.0016) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Wilms’ tumor 1 ( WT1 ) gene, whose protein product acts as a transcription factor, regulating cell development and survival and whose quantitative assessment is a useful tool to measure disease burden in AML [ 14 , 27 , 28 ], was overexpressed in either the peripheral blood or bone marrow in 17 of 19 (89.5%) evaluable BCL-2 − AML patients and in 57 of 60 (95.0%) evaluable BCL-2 + AML patients. In line with the lower bone marrow blast percentage, the WT1 transcript burden in the bone marrow was significantly lower in the BCL-2 − AML subgroup (47,910 ± 24,410 copies/µg) as compared with the BCL-2 + subgroup (148,900 ± 23,700 copies/µg; p = 0.0016) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the financial burden of venetoclax treatment and the risk of additive toxicity when combined with IC or HMAs, it is critically important to determine which patients will most benefit from the addition of venetoclax [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Next-generation sequencing (NGS) is a valuable tool that can be used to identify gene mutations conferring resistance or sensitivity to venetoclax [ 8 , 14 ]. For example, patients harboring nucleophosmin 1 ( NPM1 ) or isocitrate dehydrogenase ( IDH ) mutations consistently respond well to combined venetoclax–chemotherapy treatment [ 9 , 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the high structural similarity among the family members (until 70% in the DNA-binding domain), they can bind the same responsive promoters [ 32 , 33 , 34 , 35 ]. Thus, they share overlapping functions due to their ability to trans-activate the same genes like cyclin-dependent kinase (CDK) inhibitor ( CDKN1A (p21)), Bcl2 Binding Component 3 ( PUMA ), and Murine Double Minute 2 ( MDM2 ) [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The previous study found that WT1 transcription factor (WT1) can play a role in heart and blood vessel formation [38]. It was also regarded as a key element in acute myeloid leukemia [39], and WT1 overexpression was an independent positive prognostic factor in adult B-cell acute lymphoblastic leukemia patients [40]. The transcription factor Sp1 (Sp1) can regulate the expression of multiple genes [41], which can play a role in the body's antioxidant stress [42].…”
Section: Discussionmentioning
confidence: 99%